Recurrence Rate of Primary Pterygium Following Excision with Mitomycin C versus Excision with Amniotic Membrane Transplant: -Doi: 10.36351/pjo.v36i3.1033 - Humayun, Jawad; Rehman, Mubashir -; Farhan, Mohammad; Kamran, Muhammad Kashif; Khan, Shahid Abdur Rauf (Pakistan Journal of Ophthalmology, 2020)
Purpose: To compare recurrence rate of primary pterygium following excision with mitomycin c verses excision with amniotic membrane transplant. Study Design: Quasi experimental study. Place and Duration of Study: Qazi Hussain Ahmad Medical Complex, Nowshera, from January 2019 to June 2019. Material and Methods: One hundred and two patients presenting for the first time with pterygium were included in the study and were divided into two groups. Patients having conjunctivitis, blephritis, keratitis or any other ocular inflammatory condition and patients having history of chemical burns and symblepharon were excluded from the study. Group A underwent surgical excision with 0.02% mitomycin–C application for 3 minutes and Group B was surgically treated with application of amniotic membrane. Patients of both groups were followed up for six months to detect recurrence of pterygium. Data was analyzed using SPSS version 20. Frequency and percentages were calculated for categorical data like age, gender and recurrence rate. Recurrence rate was stratified among age and sex to see the effect modifiers. Results: Mean age in both groups was 39.98 ± 9.11 years. In group A, 64.70% patients were males and in group B, 62.74% patients were male. Recurrence of Pterygium was seen in 21.5% patients in group A and 7.84% in group B. The difference was statistically significant with a p value of 0.05. Conclusion: Recurrence rate of primary pterygium following excision with mitomycin C is higher than excision with amniotic membrane transplant